Soviet-American Academic Exchanges, 1958-1975 - Byrnes, Robert (Indiana University Press, 1976)
This volume analyzes academic exchanges between the United States and the Soviet Union, as well as some of the states of Eastern Europe, from 1958 through 1975 in the framework of Soviet-American cultural relations and of the larger Soviet-American relationship. Academic exchanges with the Soviet Union, which began formally in 1958 and which continue under many of the principles then established, have increased our understanding of the Soviet Union and have created new relationships between our universities and our government. They have often provided the closest and most significant form of personal contact between American and Soviet citizens. They have also played an important political role, although they are called the "neglected aspect" of our foreign policy. They reveal the basic philosophies and policies that separate the two systems and the adversary character of Soviet-American relations.